That straight talk: Sarah Palin and the sociolinguistics of demonstratives. (February 2014) - Acton, Eric K.; Potts, Christopher
<x xml:space="preserve">Abstract</x> Drawing on previous analyses of the social meaning of demonstratives and other function words, we argue that the semantics of demonstratives facilitates affective uses that can be characterized as attempts by the speaker to foster a sense of shared perspective and common ground with other discourse participants. We present large‐scale quantitative evidence that this strategy is widely used and communicatively effective. We then conduct a focused case study of the demonstrative use of U.S. politician and public figure Sarah Palin, situated in the wider context of Palin's persona, style, and place in the social landscape. An analysis of television interview data shows that Palin is a distinctive and prolific user of affective demonstratives. Palin's usage highlights the context‐dependence of demonstratives' social meaning and leads to a deeper understanding of her rhetorical strategies and the polarized reactions they have received.